Application of Lean Ergonomics to Reduce Motion Waste, Musculoskeletal Complaints, and Work Fatigue in Tempeh MSMEs - Endang Widuri Asih; I G. Adiatmika; I M. Muliarta; I.B. Alit Swamardika (Bali Medical and Wellness Journal, 2026)
Background: Tempeh Micro, Small, and Medium Enterprises (MSMEs) are largely home-based industries that rely on manual production processes. These manual tasks often involve inefficient movements, leading to musculoskeletal disorders and significant work fatigue. Objectives: This study aims to implement a Lean Ergonomics approach to reduce motion waste, musculoskeletal complaints, and work fatigue among workers in the tempeh industry. Method: This experimental study used a within-subject design (treatment-by-subject). The research was conducted in two phases: before improvement (P1) and after improvement (P2). Data collection involved identifying waste, analyzing work posture using the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA), measuring musculoskeletal complaints via the Nordic Body Map (NBM), and assessing fatigue levels using the Industrial Fatigue Rating Committee (IFRC) questionnaire. Results: Interventions included redesigning worktables to improve posture, implementing the 5S methodology to refine work methods, and optimizing the facility layout. The results demonstrated a significant reduction in unnecessary movements, decreasing from 15 in P1 to 7 in P2. Work posture scores improved, with RULA and REBA scores decreasing by 1.81 and 2.87, respectively. Furthermore, musculoskeletal complaints decreased by 22.4% (9.31 points), and work fatigue levels were reduced by 22.14%. Conclusion: The application of Lean Ergonomics effectively reduces motion waste, improves work posture, and lowers levels of musculoskeletal pain and fatigue. These improvements enhance overall work comfort and performance within tempeh MSMEs.